Association of Community Health Agents Celendin: an experience of social and solidarity economy. Cajamarca - García Saavedra, John (2017)
This Research-Action Project aims to show empirical evidence of social, solidarity, popular and community economy in the Association of Community Health Agents Celendin (ACOMSAC), specifically in the sector of Beekeeping Production. This associative experience located in the district of Celendín belonging to the province of Celendin in the Cajamarca region was created in 1982 and is valid until today. For the verification of our objective we will resort to some theoretical proposals within the social economy, solidarity, popular, alternative sustained under values of reciprocity with emphasis on use value instead of exchange value. To do this, we will use as a working tool the documentary and bibliographic analysis, observation and registration, semi-directed interviews with actors of the association and institutions (producers and users), and open-ended questions.